All Days 2012
DOI: 10.2118/163284-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using the Laser Irradiation to Improve the Rate of Production of Iran South West Formation

Abstract: whole level of the erosion and the resistance of rocks which were composed closured have been studied, besides, the impact of temperature and laser irradiation for more investigation about this issue has been involved before all. This subject more reveals the matter which laser absorption on the laboratory scale using laser to what extent can cause the augment of the relative permeability and secondary porosity of reservoir rock, that of the vertical and horizontal useful connectivity and eventually that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Depending on the each lithology, Poisson's ratio decreased or increased slightly but no effective. For limestone, the differences between the module of samples that been lased and the samples that hadn't be lased were less significant than each other [3] [18].…”
Section: Comparisonmentioning
confidence: 84%
See 3 more Smart Citations
“…Depending on the each lithology, Poisson's ratio decreased or increased slightly but no effective. For limestone, the differences between the module of samples that been lased and the samples that hadn't be lased were less significant than each other [3] [18].…”
Section: Comparisonmentioning
confidence: 84%
“…Because we creating hole in intact sample that could initiate many micro fractures and macroscopic hole that pass throw the whole part of sample. Other parameters such as bulk modulus and shear modulus are decreased [3]. Causes the compressibility of the samples that could evaluate to the near wellbore condition had been increased by creating on hole and many cracks inside of it [3] [19].…”
Section: Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant permeability and porosity increase was observed in low thermal conductivity limestone (Bazargan et al, 2012) Batarseh et al (2003 concluded in their study on well perforation using high power laser (COIL) that high power laser applications improved rock porosity and permeability in the perforated tunnel and in the adjacent zone. They reported that high thermal conductivity resulted in better temperature distribution in the rock, and therefore an increase in permeability and porosity.…”
Section: Effect On Permeabilitymentioning
confidence: 99%